Sarcopenia after induction therapy is associated with reduced survival in patients undergoing esophagectomy for locally-advanced esophageal cancer - Wakefield, Connor J. (J Thorac Dis, 2021)
BACKGROUND: The impact of sarcopenia on the outcome of esophageal cancer patients remains unknown in North American populations. The current study aims to investigate if sarcopenia at the time of esophagectomy for locally-advanced esophageal cancer (LAEC) is associated with survival. METHODS: Patients who underwent induction therapy followed by esophagectomy for LAEC between 2010–2018 at a single institution were identified. Exclusion criteria included follow-up less than 90 days and distant metastatic disease at the time of surgery. Demographic, treatment, and outcome data were retrospectively collected. Computed tomography (CT) scans following induction therapy were analyzed to calculate skeletal muscle index (SMI). Overall survival (OS) and disease-free survival (DFS) were examined using Kaplan-Meier and Cox Proportional Hazard regression analysis. RESULTS: Overall, 52 patients met inclusion criteria with a median BMI of 25 (IQR, 22.4–29.1) kg/m(2) and age of 65 (IQR, 57–70) years. Sarcopenia was present in 75% (39/52) of patients at the time of surgery. Sarcopenic patients had a lower median BMI and higher median age when compared to non-sarcopenic patients. There was no difference in gender, race, stage, operative technique, post-operative complications, or hospital length of stay between sarcopenic and non-sarcopenic patients. With a median follow-up of 24.9 months, patients with sarcopenia at the time of esophagectomy had worse OS [median 24.3 (IQR, 9.9–34.5) vs. 50.9 (IQR, 25.6–50.9) months, P=0.0292] and DFS [median 11.7 (IQR, 6.4–25.8) vs. 29.4 (IQR, 12.8–26.7) months, P=0.0387] compared to non-sarcopenic patients. CONCLUSIONS: Sarcopenia is associated with reduced overall and DFS in patients undergoing esophagectomy for LAEC.